Teacher-led and technology-based handwriting evaluations: A mixed-method study among Thai students in Chinese language classes - Katematu Duangmanee; Suppat Rungraungsilp; Krittiya Duangmanee (Social Sciences and Humanities Open)
The structural complexity of Chinese characters presents significant challenges in handwriting evaluation, particularly in educational contexts where accuracy and efficiency are paramount. To address the limitations of traditional assessment methods and explore the potential of technological solutions, this study compared teacher-led and Optical Character Recognition (OCR)-based assessments of Chinese handwriting, focusing on time efficiency, scoring accuracy, and teachers' perspectives on the evaluation process. Utilizing a sequential mixed-methods explanatory design, the research involved 50 Thai 12th-grade students majoring in Chinese at a public high school in Thailand, as well as three experienced Chinese language teachers. Quantitative data were collected through a paired sample t-test, which revealed that OCR assessments were significantly faster than teacher-led evaluations (Mean = .36 vs. 5.39 min; t (49) = 16.56, p < 0.001) but consistently scored lower (Mean = 24.36 vs. 31.36; t (49) = 7.3, p < 0.001). Qualitative data from thematic analysis of teacher narratives emphasized the efficiency and physical ease provided by OCR technology, though concerns were raised about its reliance on internet connectivity and inability to interpret nuanced handwriting features. Teachers expressed contrasting views, with some advocating for manual evaluation's accuracy and others favoring the hybrid use of OCR as a preliminary tool to optimize efficiency without compromising precision. The findings accentuate the potential of integrating OCR technology into handwriting assessment while addressing its limitations, offering practical implications for enhancing Chinese language instruction and evaluation in diverse educational contexts.